PELAKSANAAN UPACARA ADAT PERKAWINAN DAYAK CUPANGK DESA DI DESA KUNYIL KECAMATAN MELIAU KABUPATEN SANGGAU - NIM. A1012191137, TIARA ESA KINANTI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The Dayak Cupangk community in Kunyil Village is guided by applicable customary laws, one of which is marriage customs which are still adhered to and implemented to this day. Marriage customs are one of the ancestral traditions that are still carried out from generation to generation. However, as time went by, the Cupangk Dayak people in Kunyil Village, Meliau District, Sanggau Regency did not carry out traditional marriages according to their original customs. The formulation of the research problem is